(untitled) (New York, 1992)
The book also reviews the global state of industry, looking in detail at examples from every region of the world. Through the colorful and informative mixture of photographs, maps, and diagrams--demonstrating the wide range of industrial processes and methods--this book provides a clear understanding of the resources at industry's disposal and how these things have been harnessed.
Keywords: Natural resources,Power resources,Nguồn điện,Tài nguyên thiên nhiên